Liver Fibrosis Is Enhanced by a Higher Egg Burden in Younger Mice Infected with S. mansoni - Müller, Heike; Straßmann, Jan K.; Baier, Anne S.; von Bülow, Verena; Stettler, Frederik; Hagen, Maximilian J.; Schmidt, Fabian P.; Tschuschner, Annette; Schmid, Andreas R.; Zahner, Daniel; Köhler, Kernt; Pons-Kühnemann, Jörn; et al. (My University, 2024)
Schistosomiasis affects over 250 million people worldwide, with the highest prevalence at the age of 10–14 years. The influence of the host’s age on the severity of liver damage is unclear. We infected male 8, 14, and 20-week-old mice with S. mansoni. Hepatic damage, inflammation, fibrosis, and metabolism were analyzed by RT-qPCR, Western blotting, ELISA, immunohistochemistry, and mechanistic transwell chamber experiments using S. mansoni eggs and human hepatic stellate cells (HSCs) or primary mouse hepatocytes. Major results were validated in human biopsies. We found that hepatosplenomegaly, granuloma size, egg load, inflammation, fibrosis, and glycogen stores all improved with the increasing age of the host. However, serum alanine transaminase (ALT) levels were lowest in young mice infected with S. mansoni. Hepatic carbohydrate exploitation was characterized by a shift towards Warburg-like glycolysis in S. mansoni-infected animals. Notably, S. mansoni eggs stimulated hepatic stellate cells to an alternatively activated phenotype (GFAP+/desmin+/αSMA−) that secretes IL-6 and MCP-1. The reduction of fibrosis in older age likely depends on the fine-tuning of regulatory and inflammatory cytokines, alternative HSC activation, and the age-dependent preservation of hepatic energy stores. The current results emphasize the significance of investigations on the clinical relevance of host age-dependent liver damage in patients with schistosomiasis.
Keywords: ddc:610